ADSORPSI METILEN BIRU MENGGUNAKAN KOMPOSIT BIJI PEPAYA â ALGINAT â MAGNETIT - Wilona, Angelica
Methylene blue is a cationic dye often used in various industries. Disposal of methylene blue waste in high concentrations into water sources can harm humans and the environment due to its toxic and carcinogenic nature. Adsorption is an easy, effective, and inexpensive method to remove methylene blue from wastewater. The use of papaya seeds as an adsorbent can reduce agricultural waste in tropical countries while also saving costs for waste treatment. Magnetite is able to remove organic and inorganic pollutants from liquid waste well and provide magnetic properties to a composite. Alginate is a material often used for biosorption due to its ability to form hydrogels and other advantages, such as its low cost. In this study, composite beads made of papaya seeds, alginate, and magnetite are synthesized and characterized to use as an adsorbent for methylene blue. The synthesized adsorbent was characterized by FTIR, SEM and XRD. The adsorption of methylene blue using 0.05 grams of composite beads reached its optimum conditions at pH 4 and a contact time of 180 minutes. The adsorption process followed a pseudo second-order kinetic model and the Langmuir isotherm model. The maximum adsorption capacity was found to be 394.039 mg.g-1 . Thermodynamics study of methylene blue adsorption by composite beads showed that the process was spontaneous and endothermic, as indicated by ?G° values at 298 K, 308 K and 318 K which were found to be -4.998 kJ.mol-1 , -5.191 kJ.mol-1 and -5.383 kJ.mol-1 respectively. Values of ?H° and ?S° were found to be 0,738 kJ.mol-1 and 19.249 J.K-1mol-1 .